Regime Internacional de Propriedade Intelectual: difusão de normas TRIPS-plus - Carvalho, Pedro Henrique Mota de (2023)
This work analyzes the factors associated with the dissemination of norms in the International Intellectual Property Regime. We aim to find out why the so-called TRIPS-plus norms are disseminated, which increase protection for several areas, such as pharmaceuticals, biotechnology and cybernetic content, while reducing the flexibilities provided for in TRIPS for the formulation of public policies. We investigated the diffusion of norms through domestic and international variables. The national variables correspond to economic innovation, regulatory quality, human development and norms that restrict the protection of intellectual property in view of the public interest. The international variables are preferential trade agreements negotiated by the US, EU, EFTA and Japan. From panel data models, we found that the explanation of diffusion is multicausal and varies according to the way in which intellectual property rights are measured. Economic innovation, rules on compulsory licensing and EU agreements are the most significant variables on Ginarte and Park's (2008) index. For the intellectual property index elaborated by Morin and Gold (2014), the most significant variables are economic innovation, regulatory quality and the US and Japanese agreements